2015
DOI: 10.15451/ec2015-7-4.6-1-12
|View full text |Cite
|
Sign up to set email alerts
|

From fish and bushmeat to chicken nuggets: the nutrition transition in a continuum from rural to urban settings in the Tri frontier Amazon region

Nathalie Van Vliet,
Maria Paula Quiceno-Mesa,
Daniel Cruz-Antia
et al.

Abstract: The current contribution of wild animal proteins has been poorly quantified, particularly in the rapidly growing urban centers of tropical forests. Lack of such evidence impairs food security strategies to include the diversity of food supply inherent to traditional food systems. In this study we focus on wild sources of animal protein: wild fish and bushmeat, which have traditionally been important in people's diets in the Amazon. We compare the consumption of wild and non-wild (domestic, processed) sources o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0
8

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 52 publications
4
21
0
8
Order By: Relevance
“…Our results suggest that there is potential to increase hunting in open areas and during dry seasons, although dense vegetation with little anthropogenic disturbance is preferable for hunting specific mammals. Studies have demonstrated that peri-urban hunters commonly recognize different types of habitats for several purposes, and despite hunters' preferences for mature forest, disturbed forest has higher hunting pressure due to proximity of communities and villages, whereas mature and dense forest are more distant (Fa et al 2002, van Vliet and Nasi 2008, Mesquita and Barreto 2015. Moreover, in the Brazilian semiarid region as well as in several regions of the world, the use of motorized vehicles has been practiced not only by hunters but also by specialized middlemen in the illegal trade of bushmeat, so this contributes to overexploitation of many game species besides deforestation of the remaining vegetation of biomes (Juste et al 1995, Fa et al 2006, Di Bitetti et al 2008, Read et al 2010, Mockrin et al 2011.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that there is potential to increase hunting in open areas and during dry seasons, although dense vegetation with little anthropogenic disturbance is preferable for hunting specific mammals. Studies have demonstrated that peri-urban hunters commonly recognize different types of habitats for several purposes, and despite hunters' preferences for mature forest, disturbed forest has higher hunting pressure due to proximity of communities and villages, whereas mature and dense forest are more distant (Fa et al 2002, van Vliet and Nasi 2008, Mesquita and Barreto 2015. Moreover, in the Brazilian semiarid region as well as in several regions of the world, the use of motorized vehicles has been practiced not only by hunters but also by specialized middlemen in the illegal trade of bushmeat, so this contributes to overexploitation of many game species besides deforestation of the remaining vegetation of biomes (Juste et al 1995, Fa et al 2006, Di Bitetti et al 2008, Read et al 2010, Mockrin et al 2011.…”
Section: Discussionmentioning
confidence: 99%
“…The first step consisted of supplying self-administered questionnaires, which included a survey of meat consumption (domestic and wild) over 24 hours and information about household assets to estimate wealth (see van Vliet et al 2015a), to pupils (12 to 16 years old) from 11 schools. The survey was repeated in the wet and dry seasons; a total of 886 children in the dry season and 1046 in the wet season were questioned.…”
Section: Sampling Designmentioning
confidence: 99%
“…All these findings call attention to the ongoing process of change in the livelihood and subsistence of all coastal communities that generates a gradual reduction in the perceived availability of fish for these populations. In both rural and urban areas, changes in the way people depend of food such as fish, towards an increasing dependence of industrialized sources of animal protein can alleviate the pressures on wild species, but can have other consequences for local livelihoods and for food security, also contributing to a heavier ecological footprint (Van Vliet et al 2015). However, production of other sources of animal protein can also indirectly threat other wild species, for example, as a consequence of deforestation for livestock production.…”
Section: Main Species Consumedmentioning
confidence: 99%